Curriculum as Planned: Who Is Affected When Difference Is Marginalized? - Khan, Momina (Journal of the Canadian Association for Curriculum Studies, 2018)
How does a minority mother explain to her Canadian children the meaning of “exclusion”, “religious stigmatization” and “discrimination” when she sees her children’s identity being shaped by “structured silences” (Greene, 1993) in curriculum? Curriculum, in any time and place, becomes a contested site where debate occurs over whose values and beliefs will achieve legitimation through acceptance in the national discourse (Klieberd, 1995). My children live in liminality, as holders of hybrid identities, multiple languages, beliefs and cultures, juxtaposed against a social story of Canadian classroom teaching. Experiences such as theirs “challenge the conceptualization of curriculum as a prefabricated plan” (Wilson, Ehret, Lewkowich, & Kredl, 2017) and foreground the “blind impresses” (Rorty, 1989), gaps and silences of ideology, perceptions and practices (Rautins & Ibrahim, 2011). What are the implications when difference is censored or marginalized? By using autobiographical narrative inquiry and poetic representation, I interrogate my children’s experiences with the Canadian curriculum from the positioning of a minority parent. I explore “encounters” (Greene, 1967) through my unique lens, and propose positioning parents integrally in curriculum conversations in order to move curriculum conceptualizations from a place of binaries defined by “us” and “them”, by “dominant culture” and “minorities”, to a place of shared hope and responsibility, to a just and democratic society.